Bibliometric analysis of the brazilian periodical journal of biochemistry education. Issue 3 (19th February 2019) - do Nascimento, Agatha Santos; de Oliveira, Felipe Sales; Bianconi, M. Lucia
Abstract: The bibliometric analysis of the Brazilian periodical Journal of Biochemistry Education (JBE) covered the 117 articles published in 15 volumes in the period 2001–2017. Our results showed a positive trend in JBE publications with a significant increase in the number of articles since 2014, which can be related to the increase in research groups working in this area. The Southeast region of Brazil was the most productive one mainly due to the contribution of papers from institutions located in the State of São Paulo. Only four articles aimed the undergraduate courses (87.0%) showing methodological approaches to teach biochemistry (51.3%) and laboratory exercises (18.8%) among others. Most of the 332 authors contributed to a single article (87.7%) and just 3% of them published more than twice in JBE. The majority of the JBE articles had at least one citation in Google Scholar. There is also a great variety in the references used by the authors. Our analysis showed that JBE is an important peer reviewed publication aimed to improve teaching and learning of Biochemistry in Brazil. © 2019 International Union of Biochemistry and Molecular Biology, 47(3):249–256, 2019.